Macroeconomic imbalances evolution and their effect on bank intermediation cost in Kenya - David Ndwiga; Geraldine Makunda (Kenya Bankers Association (KBA), 2025)
The study investigates the effects of macro imbalances on the banking sector performance in Kenya from the financial intermediation cost perspective for 2020q4 - 2024q1 period. Employing dynamic panel GMM model, the study finds that inflation pressures above the upper bound target, external debt unsustainability, monetary policy tightening and current account deficit to GDP ratio lead to increase in the intermediation cost. The findings call for need to anchor the inflation rate below the upper bound target, exercise prudence fiscal measures, effective application of the monetary policy instruments and development of a matrix of interlinkages between the macro imbalances.
Keywords: 330